PENGARUH TANGGUNGJAWAB LINGKUNGAN, LEGITIMASI, DAN PELUANG DAYA SAING TERHADAP PENERAPAN ENVIRONMENTAL ACCOUNTING PADA RUMAH SAKIT DI KOTA JAYAPURA - Patma, Kurniawan; Salle, Agustinus; Pangayow, Bill J.C (Jurnal Akuntansi, Audit, dan Aset, 2018)
Environmental accounting is a term that related to how management of an organisation in doing their daily operation has an obligation to protect the environment, which also could affecting the interest parties in making decision regarding the performace of the organisation, legitimation and opportunities for competitiveness. This research aims to examine whether environmental responsibility, legitimation and opportunities for competitiveness affecting the implementation of environmental accounting at hospitals in Jayapura city. In this research, the employees of the five (5) hospitals that located in Jayapura city are concluded as research population. The sample of the population in this research is limited solely on the type of certain person who could provide particular information that could assist this research. The Quantitative approaches have been used in this study with 40 respondents as a research sampling. The result of this study has provide empirical evidence that environmental responsibility and opportunities for competitiveness in partial have significant affects on the implementation of environmental accounting. However, legitimation has not significant affect on the implementation of environmental accounting. Due to limitation of number of research sample that is collected, therefore the independent variable and the dependent variabel in this research is transformed to enhance the measurement level of ordinal scale to an interval scale. Then, the Method of Succesive Intervals is used as a tool to enhance the measurement level from ordinal scale to an interval scale that can be used as a data input in SPSS analysis.